Distinguishing Subgroups of Narcissists with Latent Class Analysis. Issue 4 (26th August 2016) - Wetzel, Eunike; Leckelt, Marius; Gerlach, Tanja M.; Back, Mitja D.
Abstract: This study investigated grandiose narcissism from a categorical perspective. We tested whether subgroups of narcissists can be distinguished that differ in their expressions of more agentic (narcissistic admiration, ADM) and more antagonistic (narcissistic rivalry, RIV) pathways of narcissism. We analysed three German samples (total N = 2211; Mage  = 26; 70% female) and one US sample (N = 971; Mage  = 35; 74% female) using latent class analysis. Four subgroups of narcissists were consistently identified across samples from Germany and the United States: low narcissists, moderate narcissists primarily characterized by agentic aspects (ADM), moderate narcissists characterized by both agentic and antagonistic aspects (ADM + RIV), and high narcissists. The subgroups were systematically related to a number of personality traits (e.g. Machiavellianism, impulsivity) and adjustment indicators (e.g. self‐esteem, empathy). Members in the moderate narcissists—ADM subgroup showed the most adaptive characteristics while members in the moderate narcissists—ADM + RIV subgroup showed the most maladaptive characteristics. Investigating grandiose narcissism—a primarily quantitative trait—from a categorical perspective can yield valuable insights that would otherwise be overlooked. In addition, our results underline the utility of a self‐regulatory process approach to grandiose narcissism that distinguishes between agentic and antagonistic dynamics. Copyright © 2016 European Association of Personality Psychology